INFLUENCE OF SOIL AND POST-EMERGENCE HERBICIDES ON THE CONTENT OF PLASTID PIGMENTS AND PRODUCTIVITY OF SOYBEAN PHOTOSYNTHETIC POTENTIAL - Dykun, O. V.; Zherebko, V. M.; Dykun, M. O. (Scientific Progress & Innovations, 2020)
The purpose of the research was to find out the nature of the effect of herbicide mixtures on soybean photosynthetic mechanism and the productivity of sowing. The experiment options included: control without weeding; control with two hand weeding; Primexstra TZ Gold (S-metolachlor, 312.5 g/l + terbuthylazine, 187.5 g/l), 4.5 l/ha; Zencor (metribuzin, 700 g/l) + Command (clomazone, 480 g/l), 0.4 l/ha+0.2 l/ha; Bazagran (bentazone, 480 g/l) + Harmony (thifensulfuron-methyl, 750 g/kg), 2.5 l/ha+0.008 kg/ha. The effectiveness of the preparations was researched in the field experiment at the separated subdivision of NUBiP of Ukraine “Agronomic Research Station” using the traditional technology for the Forest-Steppe zone of Ukraine. Soil herbicides were applied before seedlings’ emergence, and after it – when the first true leaf appeared. The pigment content was determined spectrophotometrically after extraction with DMSO (dimethyl sulfoxide) according to the method of A. Wellburn (1994). Statistical processing of received values was performed by using Excel 2016 software package. It was found that under the action of herbicides, the content of total chlorophyll in soybean leaves was by 15–20 % higher than in the control without weeding. At the same time, the phytotoxic effect of herbicides led to a decrease in the content of chlorophylls in comparison with the non-herbicidal control at double hand weeding. Furthermore, a simultaneous increase in the content of carotenoids was fixed, and it was obviously a reaction of the plants to the induced oxidative stress, resulting in inhibiting pigments’ biosynthesis. However, stress factors ensured a significant activation of photosynthetic processes, which was confirmed by the increase in a ratio of basic photosynthetic pigments. Using tank mixtures of herbicides, the ratio of a, b chlorophylls was twice as much as in both controls. The activation of the plants’ photosynthetic apparatus under the action of herbicides led to the accumulation of optimal photosynthetic potential (PP) of sown areas and ensured their higher productive capabilities. In the variant where tank mixtures of Zencor + Command and Bazagran + Harmony were used, the productivity of the PP (PPP) made 1.16 and 1.45 kg of yield per 1,000 of PP units, which was higher than the control without weeding by 28 % and 42 %, respectively. Thus, the applying of tank mixtures of selective soil and post-emergence herbicides favored the activation of photosynthetic processes in soybean plants and ensured productivity indices at the level of non-herbicidal background with hand weeding.